PENGARUH STRUKTUR MODAL, PROFITABILITAS, PERTUMBUHAN PENJUALAN TERHADAP KEBIJAKAN DIVIDEN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Zilfin Nabela Firdansiyah; Ika Wahyuni; Ardhya Yudistira Adi Nanggala (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The purpose of this study is to determine the effect of capital structure, profitability, sales growth on dividend policy with financial performance as an intervening variable. The object of this study is a pharmaceutical company listed on the Indonesia Stock Exchange in 2022-2024. The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that capital structure has a significant negative effect on financial performance, profitability has a positive insignificant effect on financial performance, sales growth has a negative insignificant effect on financial performance, capital structure has a significant negative effect on dividend policy, profitability has a negative insignificant effect on dividend policy, sales growth has a positive insignificant effect on dividend policy, financial performance has a positive insignificant effect on financial performance, capital structure has a negative insignificant effect on dividend policy through financial performance, profitability has a positive insignificant effect on dividend policy through financial performance, sales growth has a negative insignificant effect on dividend policy through financial performance.